2022
DOI: 10.1177/03010066221125864
|View full text |Cite
|
Sign up to set email alerts
|

Separate effects of auditory and visual room size on auditorium seat preference: a virtual reality study

Abstract: Audiovisual integrations and interactions happen everywhere, including in music concerts, where combined visual and auditory perception contributes to overall enjoyment. Thirty-three participants evaluated their overall subjective preference at various seats in four virtual auditoria, which comprised congruent and incongruent auditory and visual renders of two auditoria that differ only in size. Results show no significant difference between participants who completed the experiment in a fully calibrated and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 30 publications
1
8
0
Order By: Relevance
“…This effect is investigated in further studies (Y. Chen, 2022; Y. Chen et al, 2022), in which similar 3D orchestra was shown in virtual reality but with realistic auditoria renders instead of plain black background as in the current study, and results show that distance has a larger effect on preference when visual environment is present, which may be related to that visual distance perception is affected by environmental cues.…”
Section: Discussionsupporting
confidence: 58%
See 4 more Smart Citations
“…This effect is investigated in further studies (Y. Chen, 2022; Y. Chen et al, 2022), in which similar 3D orchestra was shown in virtual reality but with realistic auditoria renders instead of plain black background as in the current study, and results show that distance has a larger effect on preference when visual environment is present, which may be related to that visual distance perception is affected by environmental cues.…”
Section: Discussionsupporting
confidence: 58%
“…Some follow up studies have already verified and refined the prediction model (Y. Chen, 2022; Y. Chen et al, 2022).…”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations